TPACK Competency Analysis of Prospective Mathematics Teacher in Micro Teaching Subjects - Sartika, Nenden Suciyati; Mustika Sari, Rika Mulyati; Sopiyani, Hanifah Nurus; Yunitasari, Ika (Kreano, Jurnal Matematika Kreatif-Inovatif, 2023)
In education, the integration of technology is becoming increasingly important. This is especially true for mathematics teachers, who must use technology effectively to enhance the learning experience for their students. One method for assessing a mathematics teacher's ability to integrate technology into their teaching practice is through TPACK competency analysis. The purpose of this study was to analyze the TPACK abilities possessed by a future teacher candidate through the microteaching course he has attended. This study used a qualitative method in which data were obtained from interviews and questionnaires distributed via WhatsApp. The results of this study showed that prospective teachers who were the subjects of this study were capable and proficient enough in using and utilizing technology in learning, but were still unable to match learning methods and models with the material to be taught to students in the learning tools they compiled. Through this research, it is hoped that students who are prospective teachers of mathematics will deepen their mastery of learning methods and models which will be applied when they teach. The implications of these findings highlight the importance of increased training in developing the TPACK competency of prospective mathematics teachers.Di bidang pendidikan, integrasi teknologi menjadi semakin penting. Hal ini terutama berlaku untuk guru matematika, yang harus memanfaatkan teknologi secara efektif untuk meningkatkan pengalaman belajar bagi siswanya. Salah satu metode untuk menilai kemampuan guru matematika dalam mengintegrasikan teknologi ke dalam praktik mengajarnya adalah melalui analisis kompetensi TPACK. Tujuan dari penelitian ini untuk menganalisis kemampuan TPACK yang dimiliki oleh seorang calon guru masa depan melalui mata kuliah microteaching yang telah diikutinya.  Penelitian ini menggunakan metode kualitatif yang mana data diperoleh dari hasil wawancara dan pengisian kuisioner yang sebar melalui WhatsApp.  Hasil penelitian ini   diperoleh bahwa calon guru yang menjadi subjek penelitian ini telah mampu dan cukup mahir dalam penggunaan dan pemanfaatan teknologi dalam pembelajaran, namun masih belum mampu dalam mencocokkan metode dan model pembelajaran dengan materi yang akan diajarkan kepada siswa dalam perangkat pembelajaran yang mereka susun. Melalui penelitian ini diharapkan mahasiswa calon guru matematika dapat memperdalam penguasaannya terhadap metode dan model pembelajaran yang akan diterapkan pada saat mereka mengajar. Implikasi dari temuan ini menyoroti pentingnya peningkatan pelatihan dalam pengembangan kompetensi TPACK calon guru matematika.